The significance of FDI for innovation activities within domestic firms - The case of Central East European transition economies - Jutta Günther (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2002)
Foreign direct investment is expected to play a significant role as a multiplier of modern production- and management-know-how in Central East European transition economies. The so-called technology-spillovers are explained through externalities or extra-marketlinkages. In practice they can take place via demonstration effects, labor mobility, supplier contacts, customer contacts or networking activities. However, the empirical study on the example of Hungarian industry shows that foreign owned and domestic firms - mainly due to their strong technological disparities - build virtually separate spheres within the industrial sector. Thus, technology-spillovers do hardly appear as an innovation-stimulating means for domestic companies.
urn:nbn:de:gbv:3:2-20153
Keywords: 330; Direktinvestition; Technologietransfer; Spillover-Effekt; Übergangswirtschaft; Innovation; Dualökonomie; Ungarn